Statistical analysis of the 2014 presidential election of Costa Rica - Araya Alpízar, Carlomagno (2017)
In this paper the impact of economic conditions and demographic district and cantonal regions is analyzed. It is based on results population elections held in 2014 Costa Rica presidential election. The evidence shows relevant variables that explain the voting as: net participation rate, employment rate, urban population percentage, fertility rate and social development index. One important detail is that the highest participation and employment rate come from the population that tends to support Partido Acción Ciudadana.